Features of Diagnostics of Heart Failure and Refractory Anemia Developed on The Background of Chronic Hepatitis C - Mukhamedzhanova Mastura Khayatovna (Scholars Digest Publishing, 2023)
Chronic hepatitis C (HCV-infection) is one of the most pressing medical and social problems in the world, which is due to a wide, consistently high incidence and ubiquitous spread, as well as enormous economic costs for diagnostic and treatment processes. One of the most important problems requiring study at present is cardiohepatic syndrome (CHS).
Keywords: Chronic hepatitis C, cardiohepatic syndrome, refractory anemia, hepcidin, ferrokinetics.